Enhancement of specialized metabolites using CRISPR/Cas gene editing technology in medicinal plants - Das, Swati; Kwon, Moonhyuk; Kim, Jae-Yean (Frontiers in Plant Science, 2024)
Plants are the richest source of specialized metabolites. The specialized metabolites offer a variety of physiological benefits and many adaptive evolutionary advantages and frequently linked to plant defense mechanisms. Medicinal plants are a vital source of nutrition and active pharmaceutical agents. The production of valuable specialized metabolites and bioactive compounds has increased with the improvement of transgenic techniques like gene silencing and gene overexpression. These techniques are beneficial for decreasing production costs and increasing nutritional value. Utilizing biotechnological applications to enhance specialized metabolites in medicinal plants needs characterization and identification of genes within an elucidated pathway. The breakthrough and advancement of CRISPR/Cas-based gene editing in improving the production of specific metabolites in medicinal plants have gained significant importance in contemporary times. This article imparts a comprehensive recapitulation of the latest advancements made in the implementation of CRISPR-gene editing techniques for the purpose of augmenting specific metabolites in medicinal plants. We also provide further insights and perspectives for improving metabolic engineering scenarios in medicinal plants.